Mesenteric cyst as a presentation of chronic midgut volvulus in a 12 year old boy - E. Botchway; N. Tshifularo; M.J. Human (Elsevier, 2020)
Intestinal malrotation is a congenital anomaly of intestinal rotation and fixation that is generally symptomatic in the neonatal population. However, malrotation in an important minority is diagnosed long after infancy and is not manifested by the typical clinical manifestation of acute bilious vomiting with or without abdominal distension in an otherwise normal newborn. Here, we present a case of mesenteric cyst as a presentation of chronic midgut volvulus in a 12 year old male patient with intestinal malrotation.